The Intersection between Sex Work and Reproductive Health in Northern Karnataka, India: Identifying Gaps and Opportunities in the Context of HIV Prevention - Marissa Becker; Satyanarayana Ramanaik; Shiva Halli; James F. Blanchard; T. Raghavendra; Parinita Bhattacharjee; Stephen Moses; Lisa Avery; Sharmistha Mishra (AIDS Research and Treatment)
Objective. To examine the reproductive health practices of female sex workers (FSWs) in the context of an HIV prevention program in Karnataka, India. Methods. Data obtained from a survey of 1,011 FSWs registered with an HIV prevention program. We examined reproductive health indicators, and performed multivariate logistic regression among primiparous FSWs to assess sex work during pregnancy and antenatal HIV testing. Results. Among primiparous FSWs (N=251), 92.0% continued sex work during pregnancy, and 55.4% received antenatal HIV testing. A longer duration in sex work (AOR 2.7, 95% CI: 1.0–7.5), rural residence (AOR 3.3, 95% CI: 1.2–8.9), and antenatal HIV testing (AOR 6.3, 95% CI: 2.0–20.1) were associated with continued sex work during pregnancy. Older FSWs (age >25 years, AOR 0.12, 95% CI: 0.05–0.33), who delivered at home (AOR 0.14, 95% CI: 0.09–0.34), were least likely to receive antenatal HIV testing. Antenatal HIV testing was associated with awareness of methods to prevent vertical HIV transmission (AOR 3.9, 95% CI: 1.9–14.1). Conclusions. Antenatal HIV testing remains low in the context of ongoing sex work during pregnancy. Existing HIV prevention programs are well positioned to immediately integrate reproductive health care with HIV interventions targeted to FSWs.